Analysis of Consumer Buying Interest, which is Influenced by Online Customer Reviews and Price Consciousness - Hakim, Lukman Abdul Azizul (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to determine the effect of online customer reviews or Online Customer Review (X1) and Price Consciousness (X2) on Buying Interest (Y) studies conducted on consumers who have bought pastry products online on various online sales platforms. The survey was conducted using questionnaires to pastry consumers who had transacted through online sales platforms. After that, the data is processed using SPSS. This study used the following data analysis: coefficient of determination, t test, multiple regression test, and data quality test. Based on the results of this study, the t-count value was 4,843 sig values. 0.000 less than 0.05 indicates that online customer reviews have an impact on buying interest as well as Price Consciousness has an influence on buying interest, which is indicated by the calculation results with a calculated t value of 3.651, and a sig value. 0.001 less than 0.05.